Genetic and Genomic Analysis of Rhizoctonia solani Interactions with Arabidopsis; Evidence of Resistance Mediated through NADPH Oxidases - Foley, R.; Gleason, C.; Anderson, J.; Hamann, T.; Singh, Karambir (Public Library of Science, 2013)
Rhizoctonia solani is an important soil-borne necrotrophic fungal pathogen, with a broad host range and little effective resistance in crop plants. Arabidopsis is resistant to R. solani AG8 but susceptible to R. solani AG2-1. A screen of 36 Arabidopsis ecotypes and mutants affected in the auxin, camalexin, salicylic acid, abscisic acid and ethylene/jasmonic acid pathways did not reveal any variation in response to R. solani and demonstrated that resistance to AG8 was independent of these defense pathways. The Arabidopsis Affymetrix ATH1 Genome array was used to assess global gene expression changes in plants infected with AG8 and AG2-1 at seven days post-infection. While there was considerable overlap in the response, some gene families were differentially affected by AG8 or AG2-1 and included those involved in oxidative stress, cell wall associated proteins, transcription factors and heat shock protein genes. Since a substantial proportion of the gene expression changes were associated with oxidative stress responses, we analysed the role of NADPH oxidases in resistance. While single NADPH oxidase mutants had no effect, a NADPH oxidase double mutant atrbohf atrbohd resulted in an almost complete loss of resistance to AG8, suggesting that reactive oxidative species play an important role in Arabidopsis's resistance to R. solani.